Tipificacion de los recortes de carne de cerdo - Hortos, M.=700 1 Diestre, a.; Casademont, A.; Monfort, J.M.
(En, Es)
ilus., 9 ref.
Keywords: CARNE DE CERDO; COMPOSICION QUIMICA; PH; HUMEDAD; PROTEINAS; HIDROXIPROLINA; GRASAS; FOSFATOS; CENIZAS; ESPAÑA; TIPIFICACION; RECORTE DE CARNE